2007
DOI: 10.1177/1087054706288102
|View full text |Cite
|
Sign up to set email alerts
|

Family Characteristics of Anxious ADHD Children

Abstract: Findings are consistent with the notion that an insular, dependent, and somewhat controlling family environment characterizes families of children with ADHD and comorbid childhood anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
4
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 18 publications
5
28
4
3
Order By: Relevance
“…However, these results were not replicated in a study by Kepley and Ostrander, which did not find elevated rates of psychopathology in parents of children with ADHD and anxiety, except for higher rates of maternal substance/alcohol abuse [51]. Among these families, the family environment was described as more controlling, dependent, and discouraging of autonomy though they did not differ from the ADHD-only group in terms of family cohesion [51]. These preliminary results require replication in order to better describe the family characteristics that are uniquely associated with comorbid ADHD and anxiety disorder, given the inconsistency of findings between existing studies.…”
Section: Anxietymentioning
confidence: 57%
See 1 more Smart Citation
“…However, these results were not replicated in a study by Kepley and Ostrander, which did not find elevated rates of psychopathology in parents of children with ADHD and anxiety, except for higher rates of maternal substance/alcohol abuse [51]. Among these families, the family environment was described as more controlling, dependent, and discouraging of autonomy though they did not differ from the ADHD-only group in terms of family cohesion [51]. These preliminary results require replication in order to better describe the family characteristics that are uniquely associated with comorbid ADHD and anxiety disorder, given the inconsistency of findings between existing studies.…”
Section: Anxietymentioning
confidence: 57%
“…This study highlights the importance of carefully examining for mediating and moderating variables in order to interpret the pattern of associations found between family and child correlates. However, these results were not replicated in a study by Kepley and Ostrander, which did not find elevated rates of psychopathology in parents of children with ADHD and anxiety, except for higher rates of maternal substance/alcohol abuse [51]. Among these families, the family environment was described as more controlling, dependent, and discouraging of autonomy though they did not differ from the ADHD-only group in terms of family cohesion [51].…”
Section: Anxietymentioning
confidence: 70%
“…Recently, however, a few studies have reported increased disruption in families of children with anxiety plus comorbid disorders. For instance, parents of children with anxiety disorders and medical comorbidities, compared to those without comorbidities, reported higher levels of caregiver strain (Chavira et al 2008); children with comorbid anxiety and depressive disorders report greater family dysfunction and problematic affective responsiveness compared to children with anxiety disorders alone (Guberman and Manassis 2011;O'Neil et al 2010), and families with children who have anxiety disorders and ADHD have been characterized as having higher levels of overprotection, overcontrol, and conflict and lower levels of cohesion compared to families without comorbidities (Kepley and Ostrander 2007;Pfiffner and McBurnett 2006). Future studies are needed to assess the impact of psychiatric and medical comorbidities and determine the direction of the impact (i.e., whether children reared in dysfunctional families have a greater risk for developing comorbid conditions or whether family functioning suffers in response to children who are more impaired due to having multiple conditions).…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…Moos and Moos (1994) reported internal consistencies for the FES Real Form sub-scales as ranging from .61 to .78 and test-retest reliability as ranging from .68 to .86. The FESChinese version has been used on rural residents in China to explore the relationship between family environment factors and suicide risks (Lu et al 2001;Wang and Zhang 2001) and continues to be used in the literature to explore family functioning in relation to a variety of clinical issues that include sexual abuse (Kenny and Mceachern 2007), psychiatric relapse (Karamlou et al 2010), ADHD (Guo et al 2008;Kepley and Ostrander 2007) and substance abuse (Bidokhti et al 2006).…”
Section: Instrumentationmentioning
confidence: 99%